2016
DOI: 10.3390/rs8080652
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Subsidence Monitoring Associated with Land Reclamation Using the Point Target Based SBAS-InSAR Method: A Case Study of Shenzhen, China

Abstract: Shenzhen, the first special economic zone of China, has witnessed earth-shaking changes since the late 1980s. In the past 35 years, about 80 km 2 of land has been reclaimed from the sea in Shenzhen. In order to investigate coastal vertical land motions associated with land reclamation, we proposed an elaborated Point Target (PT) based Small Baseline Subset InSAR (SBAS-InSAR) strategy to process an ENVISAT ASAR ascending and descending orbits dataset both acquired from 2007 to 2010. This new strategy can not on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 50 publications
2
80
2
Order By: Relevance
“…As Figure 2 shows, small scale subsidence is scattered across the city. The scattered subsidence was caused by tunnel excavation during subway construction, with slow soil consolidation around the tunnel, and the cyclic loading of trains [16,18]. Compared with the ASAR data results (Figure 2), the PALSAR results had higher PT density and coherence, benefiting from the better penetration of the L-band satellite.…”
Section: Ground Subsidence Of the Guangzhou Subway Networkmentioning
confidence: 82%
See 1 more Smart Citation
“…As Figure 2 shows, small scale subsidence is scattered across the city. The scattered subsidence was caused by tunnel excavation during subway construction, with slow soil consolidation around the tunnel, and the cyclic loading of trains [16,18]. Compared with the ASAR data results (Figure 2), the PALSAR results had higher PT density and coherence, benefiting from the better penetration of the L-band satellite.…”
Section: Ground Subsidence Of the Guangzhou Subway Networkmentioning
confidence: 82%
“…Ground subsidence along subways have also been observed in other delta areas, such as Shenzhen [18], Shanghai [17,41], Beijing [19,42,43], and Mexico [44,45]. In different areas, the ground subsidence scales and magnitudes are different.…”
Section: Subsidence Along Subway Lines In Delta Areasmentioning
confidence: 99%
“…Actually, it has been widely used and its superiorities shown in detecting time-series surface deformation over many peninsulas and delta areas, such as the Mexico City [8], Shanghai [9], and Indonesia [10]. Traditional temporal InSAR methods, such as Persistent Scatterer Interferometry (PS-InSAR), IPTA (Interferometric Point Target Analysis), and Small Baseline Subset (SBAS-InSAR) have been applied in detecting surface deformation, but they need abundant SAR images in data processing [11][12][13]. As the datasets are very limited in our study area, we used a modified stacking method to measure the surface deformation evolution over the whole LZP with three kinds of SAR images (JERS, ENVISAT and ALOS1) acquired from 1992 to 2010.…”
Section: Hydrogeological Settingmentioning
confidence: 99%
“…The combination of land lowering with rising water levels due to global sea-level rise can make coastal areas especially vulnerable to flooding [33]. Two papers in this Special Issue study land subsidence in coastal areas [34,35]. Cianflore et al [34] analyze different causes contributing to land subsidence observed in the ancient Greek colony of the Sibari Plain (Southern Italy) using ENVISAT ASAR and Cosmo-SkyMED images.…”
Section: Land Subsidence Hazardsmentioning
confidence: 99%
“…Cianflore et al [34] analyze different causes contributing to land subsidence observed in the ancient Greek colony of the Sibari Plain (Southern Italy) using ENVISAT ASAR and Cosmo-SkyMED images. Xu et al [35] focus on the land subsidence affecting the land reclaimed from the sea in Shenzhen (SE China). These authors use a Point Target based Small Baseline Subset InSAR approach to process ascending and descending ENVISAT ASAR images acquired during the period from 2007 to 2010, and observe subsidence rates up to 25 mm/year.…”
Section: Land Subsidence Hazardsmentioning
confidence: 99%